EXPLORATION OF THE CONTRIBUTION OF SMES TO ECONOMIC GROWTH IN EAST JAVA PROVINCE 2020-2022 - Agustina, Putriani; Fitriyanto, Doni (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2024)
The purpose of this study is to examine the effect of the number of MSME units on economic growth in East Java Province, to examine the effect of MSME labor on economic growth in East Java Province, and to examine the effect of the number of MSME units and MSME labor on economic growth in East Java Province. This study uses a quantitative approach with an associative type. The data sources used are secondary data obtained from the publications of the East Java Central Statistics Agency. The data analysis technique employs multiple regression analysis with the help of the Eviews application. The population and sample consist of cities/regencies in East Java from 2020-2022. The results of the study show that: The number of MSME units partially affects economic growth in East Java Province from 2020-2022. The number of MSME laborers partially does not affect economic growth in East Java Province from 2020-2022. However, the number of MSME units and the number of MSME laborers together (simultaneously) affect economic growth in East Java Province from 2020-2022 .